Domestic science in county high schools - Christensen, Esther E. (My University, 1908)
Introduction: The ideal location for a school building in which Domestic Science is taught is in the center of the block with at least sixty feet of air space around it so as to give sufficient light and sunshine. A room in the south east corner on the first floor is the most desirable as there is the benefit of the morning sun and the afternoons will be cool.
Citation: Christensen, Esther E. Domestic science in county high schools. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Education; High Schools; Home Economics; Graduating theses; Senior theses; Theses